Genetic association of ACE I/D and ACTN3 R577X polymorphisms with sports performance among Malay male secondary school students - Hock, Chia Boon (2018)
Sports performance is influenced by the interaction of environmental and polygenic factors, characterising inter-individual variability. Sixty six percentage of the differences in athletic ability is influenced by hereditary factors, while the 34 % differences are due to individual environmental factors. Therefore, exploration of the individual genetic variation on the sports performance has been an area of research interest. The aim of this study was to determine the association between ACTN3 R577X and ACE I/D polymorphisms with sports performance in Malay male secondary school students. This study was divided into 2 phases. In phase 1, physical activity of the participants were recorded based on teacher’s recommendation and the International Physical Activity Questionnaire (IPAQ). Sedentary subjects were recruited when their IPAQ scores were less than 600 MET-min per week while sprinttype and endurance-type subjects were recruited when their scores were more than 600 MET-min per week. Physical fitness tests (30 (meter) m sprint test and 20 m shuttle run test) were conducted to confirm subject’s sprint, endurance and sedentary status. In phase 2, genotyping was performed for ACTN3 R577X and ACE I/D polymorphisms by using PCR and RFLP methods. Differences in the frequencies of genotypes and alleles of the ACTN3 and ACE genes between sprint, endurance and sedentary subjects were analysed using one-way ANOVA test. The associations between the ACTN3 R577X and ACE I/D genotype, singly and in combination wereanalysed using the conditional logistic regression by deriving odds ratio (OR) and 95 % (confidence interval) CIs. There were 382 Malay males aged 16-17 years recruited as participants in this study (n = 120 for sprint-type subjects, n = 131 for endurancetype subjects and n = 131 for sedentary subjects). No significant difference in the frequencies of ACTN3 R577X genotypes and alleles was found among sprint-type subjects, endurance-type subjects and sedentary subjects. Significant difference was observed for the frequencies of DD genotype of ACE gene among sprint-type subjects, endurance-type subjects and sedentary subjects. Significant association was observed between II genotype (OR: 5.277, 95 % CI: 1.845 – 15.090, p = 0.002), ID genotype (OR: 3.312, 95 % CI: 1.165 – 9.423, p = 0.025) as well as combination of II and ID genotypes (OR: 4.144, 95 % CI: 1.503 – 11.425, p = 0.006) and sprint performance. It is suggested that subjects with I allele of ACE gene is more likely to be associated with sprint performance. However, no significant association was observed between ACTN3 R577X genotypes and sports performance. The data from this study can provide further insights into understanding the physiological changes to sports performance. However, more work is needed to explore these findings using larger samples from different states of Malaysia and analyses on a greater number of polymorphisms for better understanding of the relationship between the polymorphisms and sports performance.